Charismatic Authority of Labai Religious Figures in Malay-Sambas Community in West Kalimantan - Sahri sahri (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Amid a dynamic social change in modern times, religious leaders still carry out several critical societal roles and functions. The emergence of this situation is mainly due to the absence of new social institutions that can completely replace them. This study, therefore, aims to explain Labai's role as a religious and community figure in the Malay-Sambas community in West Kalimantan Province. This study uses Weber's concept of charisma to analyze the role and function of Labai in the Malay-Sambas society. A qualitative method with an ethnographic approach was applied to analyze the data collected through in-depth interviews with some Labai. The results of this study indicate that the charisma authority of Labai was built with the legitimacy of the Malay-Sambas community who positioned Labai as a public figure who not only played a role as a religious figure in charge of providing religious understanding or religious doctrine to the community but also as a community figure who is always stand-by when its members needed help. In this case, Labai plays a vital role in maintaining local wisdom that has been preserved for generations in the Malay-Sambas community in West Kalimantan.